A comprehensive analysis on a novel DC‐Excited Flux‐Switching Linear Motor as a new linear vehicle for transportation systems. Issue 1 (7th August 2022) - Farhadi, Ali; Yousefi, Hossein; Noorollahi, Younes; Hajinezhad, Ahmad
Abstract: A novel DC‐Excited Flux‐Switching Linear Motor (DC‐FSLM) is investigated in this paper, where a simple secondary is used as the machine stator. The phases and excitation windings are placed on the primary, which contributes to a low‐cost and simple structure linear motor with acceptable dynamic performance. The motor operation under dynamic load is analysed by a parametric Magnetic Equivalent Circuit (MEC), and the core saturation is modelled by the non‐linear reluctance of the flux tubes. Moreover, the end‐effect is considered by virtual zones at both entrance and exit ends of the primary. In the considered MEC, the model accuracy can be selected as desired as well as different DC‐FSLMs with various properties can be modelled. Finally, the machine capabilities and performance characteristics are discussed by simulation results, and validation is performed by the Finite Element Method (FEM).